2008
DOI: 10.1038/oby.2008.19
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Weight Loss in Overweight Middle‐aged Women Through the Internet

Abstract: Objective: The purpose of this study was to compare weight regain in a group of perimenopausal women (48.0 ± 4.4 years old), randomized to a 12-month weight maintenance Internet intervention or to self-directed weight maintenance after a 4-month weight loss treatment. Methods and Procedures: After a 4-month behavioral weight loss program, 135 women were randomized to either Internet or self-directed groups. The Internet group (n = 66) used a website to gain information and complete logs concerning their weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
187
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(192 citation statements)
references
References 34 publications
2
187
2
1
Order By: Relevance
“…Moreover, another finding from the stratified analyses was that the Web-based programs did not have a significant additional weight-loss effect unless their use was combined with face-to-face support. These results suggest that an in-person contact 29 Instruction, self-monitoring and counseling Counseling, self-monitoring or only material Maintenance Cussler et al 30 Instruction, self-monitoring and counseling Self-directed Maintenance Hunter et al 31 Instruction, self-monitoring and counseling Counseling via phone Self-help Loss Digenio et al 32 Counseling Material Material with counseling (via phone or face-to-face) or only material Loss Patrick et al 18 Instruction Counseling Material Loss van Wier et al 19 Instruction and counseling Material Material Loss Morgan et al 33 Instruction and self-monitoring Material Loss Ueki et al 34 Instruction and self-monitoring Instruction via fax/mail and supplemental food (jelly) Effect of lifestyle modification on weight control S Kodama et al approach is superior to a technology-based approach from the viewpoint of the amount of weight loss; if used, an Internet program needs to include the component of a faceto-face program for participants to achieve weight loss. It is known that social support is one of the important aspects of behavioral obesity treatment and is associated with better weight-loss outcomes.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, another finding from the stratified analyses was that the Web-based programs did not have a significant additional weight-loss effect unless their use was combined with face-to-face support. These results suggest that an in-person contact 29 Instruction, self-monitoring and counseling Counseling, self-monitoring or only material Maintenance Cussler et al 30 Instruction, self-monitoring and counseling Self-directed Maintenance Hunter et al 31 Instruction, self-monitoring and counseling Counseling via phone Self-help Loss Digenio et al 32 Counseling Material Material with counseling (via phone or face-to-face) or only material Loss Patrick et al 18 Instruction Counseling Material Loss van Wier et al 19 Instruction and counseling Material Material Loss Morgan et al 33 Instruction and self-monitoring Material Loss Ueki et al 34 Instruction and self-monitoring Instruction via fax/mail and supplemental food (jelly) Effect of lifestyle modification on weight control S Kodama et al approach is superior to a technology-based approach from the viewpoint of the amount of weight loss; if used, an Internet program needs to include the component of a faceto-face program for participants to achieve weight loss. It is known that social support is one of the important aspects of behavioral obesity treatment and is associated with better weight-loss outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…Table 2 shows details of the obesity treatment programs in each included study. To summarize the study-specific Webbased programs in terms of the role of the Internet, 16 studies [18][19][20][23][24][26][27][28][30][31][33][34][35][36][38][39] used the Internet as an adjunct to the non-Web-based obesity care support provided in both control and experimental groups. One study 25 used it as a substitute for face-to-face counseling.…”
Section: Data Synthesismentioning
confidence: 99%
“…Other interventions sought to increase fibre intake, 44,45,55,59,[80][81][82] Comparators used in included studies Table 4 shows a summary of comparators used in the studies. Fourteen studies 44,[48][49][50][51]53,54,56,59,69,74,77,79,80 trialled the intervention against a non-intervention control group. Three studies 47,55,58 used attention controls, whereby participants in the control group received non-adaptive information on a similar topic, or received a similarly interactive intervention, but on an unrelated health topic.…”
Section: Target Outcomes Of Included Studiesmentioning
confidence: 99%
“…All e-learning interventions were delivered in high-income countries, and the majority of interventions were delivered in the USA [42][43][44][45][47][48][49][50][51][52][53]55,56,58,59,62,64,66,[70][71][72][73][74][75][80][81][82][83][84] research groups dedicated to e-learning and diet research; hence, the geographic clustering of studies. For example, a single large e-learning research group produced all eight RCTs set in the Netherlands and Belgium.…”
Section: 83mentioning
confidence: 99%
“…[15][16][17][18] To overcome some of these barriers, an increasing number of weight loss interventions have used computer technology to deliver education, support, and self-monitoring strategies. [19][20][21][22] It has been suggested that the interactive nature of computers provides a persuasive advantage when compared to other media 23 and assists social learning by providing users with feedback, modeling of desired attitudes or behaviors, and social dynamics and support. 24,25 Such interventions have been found to be useful in treating a variety of conditions including depression 26 and post-traumatic stress disorder, 27 and in promoting self-management of chronic disease.…”
mentioning
confidence: 99%